The Role of PKn and Installing National Values in Elementary Schools - Afriza, Dinda (International Journal of Students Education, 2025)
This study aims to describe the role of educators in instilling national values through learning. Citizenship Education (PKn) to students and explain the efforts of educators in instilling honesty values to students. This type of research is qualitative by analyzing the phenomena and meanings contained in national values. Data collected through interviews, observations and documentation, then the data is analyzed with several steps of utilization, categorization, data intervention, then the data is validated by extending the observation period and triangulation. The results of the study showed a change in attitudes and honest behavior of students not cheating on tests to their friends. returning library books on time, being able to honestly state the reasons for not coming to school. being honest when shopping in the canteen, becoming a knowledgeable, disciplined, and sporty person. In theory, this study aims to analyze and find out to what extent the role of Citizenship Education subjects in implementing Pancasila values in Elementary School children. This research is a qualitative study. The data collection technique uses documentation, articles, journals, books, news. and official statements of the organization. Data analysis using Triangulation